Принципы моделирования РБД со звездообразной топологией - Петров, Э. Г.; Самойленко, Н. В. (ХНУРЭ, 2008)
In the given work is investigated the problem of modeling of the distributed databases (DDB) with the star topology. We consider DDM as an object of modeling. The main tool for solving this problem is analytical-simulation method that is based on the combination of analytical and simulation methods. Theoretical fundamentals of methods are queuing system that is held with the help of the Q-scheme.
Keywords: моделирование РБД